The relationship between anthropometric indicators for malnutrition status, and blood pressure parameters in Ellisras rural children aged 5 to 12 years: Ellisras longitudinal study - Ramoshaba, Nthai Elfas (My University, 2016)
Cardiovascular diseases (CVDs) are major public health problems nowadays in Africa. From prospective studies, it is also known that risk factors for CVDs start early in life and increase morbidity and mortality in sub-Saharan African adults. Mostly the risk factors of CVDs are malnutrition and hypertension. Economic development in South Africa leads to lifestyle changes that contribute to a high prevalence of high blood pressure (BP) and malnutrition. However, little is known about the relationship of anthropometric indicators and BP in children from the developing countries. Therefore the aim of this study was to determine the association between anthropometrics indicators and BP among rural children in Ellisras area of Limpopo province, South Africa. All 1961 children (n=1029 boys, n=932 girls) aged 5-12 years underwent anthropometric and BP measurements using standard procedure. Receiver operating characteristics (ROC) curve was used to assess the ability of anthropometric indicators to discriminate children with high BP. ROC was used to determine the area under curve (AUC), cut-off value, sensitivity and specificity for underweight in children for each age and gender. Linear regression was used to assess the relationship between anthropometric indicators and BP. ROC curve showed that height (AUC = 0.700, 95%Cl 0.581 to 0.818), SH (AUC= 0.690, 95%Cl 0.573 to 0.786) and SH/H (AUC=0.670, 95% 0.533 to 0.807) can significantly (P<0.05) identify Ellisras children with hypertension. AUC for neck circumference (NC) (0.698), mid upper arm circumference (MUAC) (0.677) and body mass index (BMI) (0.636) for boys were statistically significant (P<0.05) for high systolic blood pressure (SBP), while in girls AUC of BMI was not significant (P>0.05) for high diastolic blood pressure (DBP). The regression analysis showed a positive significant (P<0.05) association of SBP with NC (β=0.764, 95%CI 0.475 to 1.052) and MUAC (β=1.286, 95% Cl 0.990 to 1.581) for unadjusted and adjusted age and gender. NC (β=0.628 95% Cl 0.303 to 0.953) and MUAC (β=1.351 95% CI 1.004 to 1.697) showed a significant association with SBP. However, MUAC had a significant association with DBP for both unadjusted and adjusted age and gender. Sitting height (SH) was significantly associated with SBP (β = 0.134, 95% Cl 0.210 to 0.416) and DBP (β = 0.088, 95% Cl 0.086 to 0.259) for unadjusted. After adjusted for age and gender, SH was significantly associated with both SBP (β = 0.161, 95% Cl 0.220 to 0.532) and DBP (β = 0.101, 95% Cl 0.066 to 0.329). There was a positive significant association between BP and anthropometric indicators in this population study, though the association of DBP and NC disappeared after adjustments for age and gender. Furthermore, there is a positive significant association between DBP and SBP with the components of height amongst Ellisras rural children. NC and MUAC are the simplest techniques with good interrater reliability and could be used to screen underweight in children.
Thesis (M.Sc. (Physiology)) -- University of Limpopo, 2016
Keywords: Malnutrition; Neck circumference; Mid upper circumference; Cardiovascular disease; Blood pressure; Components of height; Rural South African children; Malnutrition in children; Cardiovascular system -- Diseases; Hypertension; Hypertension in children